Peningkatan Kompetensi Pustakawan dan Optimalisasi Teknologi Informasi untuk Meningkatkan Pelayanan bagi Pengguna Difabel di Perpustakaan Perguruan Tinggi - Rizka, Fithria; Maulida Zakiah, Diana; Arifin, Muhammad (Forum Perpustakaan Perguruan Tinggi Indonesia, 2023)
All citizens, including people with disabilities, have the right to receive equal education. College libraries must play an important role in supporting this right by providing inclusive services to all users, including those with disabilities. However, until now, many libraries are not fully ready to provide services to users with disabilities, both in terms of infrastructure and human resources. This can hinder the learning process for those with disabilities. This research aims to increase institutional awareness about the importance of inclusivity in university libraries, by emphasizing that people with disabilities are an integral part of the academic community. Persons with disabilities have the same rights to learning support facilities and services. Therefore, every university library must be inclusive and able to serve users with disabilities well. Librarians are also required to have special competencies, both soft skills and hard skills, to serve readers with disabilities so that they experience ease in utilizing library services. The research method used is a literature review by examining various scientific reference sources, including printed books, electronic books, articles and news. The results of this research show that to create a disability-friendly university library, elements such as adequate facilities and infrastructure, assistive technology, librarian competence, and an effective outreach program are needed. By implementing these elements, libraries can become more inclusive and provide optimal services for all users, including people with disabilities.